Real-world healthcare costs of localized and regionally advanced cutaneous melanoma in the Netherlands. Issue 3 (12th April 2021) - Leeneman, Brenda; Blommestein, Hedwig M.; Coupé, Veerle M.H.; Hendriks, Mathijs P.; Kruit, Wim H.J.; Plaisier, Peter W.; van Ruth, Serge; ten Tije, Albert J.; Wouters, Michel W.J.M.; Franken, Margreet G.; Uyl - de Groot, Carin A.
Abstract : Supplemental Digital Content is available in the text. Abstract : The aim of this study was to provide insight into real-world healthcare costs of patients initially diagnosed with localized or regionally advanced melanoma in three Dutch hospitals between 2003 and 2011. Patients were stratified according to their stage at diagnosis and recurrence status. Costs were calculated by applying unit costs to individual patient resource use and reported for the full disease course, the initial treatment episode, and treatment episodes for disease recurrence (stratified by type of recurrence). We included 198 patients with localized melanoma and 98 patients with regionally advanced melanoma. Total costs were much higher for patients with disease recurrence than for patients without disease recurrence: €20 007 versus €3032 for patients with localized melanoma and €19 519 versus €5951 for patients with regionally advanced melanoma. This was owing to the costs of disease recurrence because the costs of the initial treatment were comparable between patients with and without disease recurrence. Costs of disease recurrence were dependent on the type of recurrence: €4414, €4604, €8129 and €10 393 for a local recurrence, intralymphatic metastases, regional lymph node metastases and distant metastases, respectively. In conclusion, healthcare costs of patients with localized and regionally advanced melanoma were rather low for the initial treatment. Costs became, however, more substantial in case of disease recurrence. In the context of a rapidly changing treatment paradigm, it remains crucial to monitor treatment outcomes as well as healthcare expenditures.